Conceptual metaphor in the English-speaking medical discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article examines the recommendations and guidelines for allergy and asthma treatment of European Academy of Allergy and Clinical Immunology (EAACI). The analyzed texts reveal the productive functioning of the metaphorical model TREATING ILLNESS IS FIGHTING A WAR which in turn falls into a number of derivative conceptual metaphors.
Keywords: conceptual metaphor; medical discourse; allergology; immunology